Feature Selection Stability and Accuracy of Prediction Models for Genomic Prediction of Residual Feed Intake in Pigs Using Machine Learning - Piles, Miriam; Bergsma, Rob; Gianola, Daniel; Gilbert, Hélène; Tusell, Llibertat (Frontiers in Genetics, 2021)
Feature selection (FS, i.e. selection of a subset of predictor variables from input data) is essential in high-dimensional datasets to prevent overfitting of prediction/classification models and reduce computation time and resources. In genomics, FS allows identifying relevant markers and designing low-density SNP chips to evaluate selection candidates. In this research, several univariate and multivariate FS algorithms combined with various parametric and non-parametric learners were applied to the prediction of feed efficiency in growing pigs from high-dimensional genomic data. The objective was to find the best combination of feature selector, SNP subset size and learner leading to accurate and stable (i.e. less sensitive to changes in the training data) prediction models. GBLUP without SNP pre-selection was the benchmark. Three types of FS methods were implemented: i) filter methods: univariate (univ.dtree, spearcor) or multivariate (cforest, mrmr), with random selection as benchmark; ii) embedded methods: elastic net and LASSO regression; iii) combination of filter and embedded methods. Ridge Regression, Support Vector Machine (SVM) and Gradient Boosting (GB) were applied after pre-selection performed with the filter methods. Data represented 5,708 individual records of residual feed intake to be predicted from the animal’s own genotype. Accuracy [stability of results] was measured as the median [interquartile range] of the Spearman correlation between observed and predicted data in a 10-fold cross validation. The best prediction in terms of accuracy and stability was obtained with SVM and GB using 500 or more SNPs (0.28 [0.02] and 0.27 [0.04] for SVM and GB with 1,000 SNPs, respectively). With larger subset sizes (1,000 – 1,500 SNPs), the filter method had no influence on prediction quality, which was similar to that attained with random selection. With 50 - 250 SNPs, the FS method had a huge impact on prediction quality: it was very poor for tree-based methods combined with any learner, but good and similar to what was obtained with larger SNP subsets when spearcor or mrmr were implemented with or without embedded methods. Those filters also led to very stable results, suggesting their potential use for designing low-density SNP chips for genome-based evaluation of feed efficiency.